Employment and Social Trends by Region. Issue 1 (7th October 2016) - ,
Abstract : Labour market and social conditions vary considerably across regions. In terms of unemployment, the short‐term outlook shows that Europe and Central Asia and Northern America will do relatively well in comparison to other regions, including Latin America and the Caribbean, the Arab States, Asia, and Sub‐Saharan Africa. However, unemployment levels and rates do not often capture well the extent of the labour market and social challenges. This is particularly the case in the emerging and developing economies, where the persistence of vulnerable employment, informal employment and working poverty is of key concern (ILO, 2015i). Even in Europe and Central Asia and Northern America, where unemployment is expected to decline, long‐term unemployment and youth unemployment remain significant labour market and social challenges. In this respect, all countries and regions of the world are confronting the challenge of creating sufficient quality employment. With that in mind, this chapter will assess both across and within regions (i) recent economic and labour market developments; (ii) short‐term employment and social prospects; and (iii) major deficits and challenges to achieving success in terms of the SDGs.